Struvite Crystallization Control with Addition of Maleic Acid in Liquid Waste as Fertilizer Materials - Perwitasari, D. S.; A. P. Bayuseno; J. Jamari; S. Muryanto (Nusantara Science and Technology Proceedings)
Struvite was magnesium ammonium phosphate (MgNH4PO4.6H2O) in the form of white orthorhombic crystals. In aqueous solutions containing Mg2+, NH4+ and PO42- in the equivalent amount of 1: 1: 1 molar ratio, struvite crystallization can occur spontaneously with the influence concentration maleic acid, temperature and stirred speeds. Struvite was a mineral crystal commonly found in pipes, pumps and other industrial equipment. Deposition of struvite can interfere with equipment performance and cause increased maintenance costs. The experiment was carried out in a batch process using 500 ml of mechanical glass at 200, 300 and 400 rpm. Maleic acid concentration as an additive 0.0; 1.0; 10.0; and 20.0 ppm in solution at 30oC and 40oC. The more amount of additive maleic acid concentration added, the smaller the rate constants value. By decreasing the constant rate, the growth of struvite crystals also decreases so that the growth of struvite crystals becomes inhibited, but different for stirring, the higher the stirred speeds the rate constants will increase so that crystal growth also increases. The crystals obtained were characterized using SEM-EDX and XRPD Rietveld. Characterization results show that struvite was the main crystal. The morphology of crystals was prismatic. The research has been carried out to increase understanding of the extraction of phosphate from industrial wastewater through struvite crystallization and was useful in prospective wastewater treatment technologies for phosphat recovery and has the potential that can be used as fertilizer.